2021
DOI: 10.3390/en14165008
|View full text |Cite
|
Sign up to set email alerts
|

Do Perceived Risk, Perception of Self-Efficacy, and Openness to Technology Matter for Solar PV Adoption? An Application of the Extended Theory of Planned Behavior

Abstract: Solar PV (photovoltaic) technology has gained considerable attention worldwide, as it can help reduce the adverse effects of CO2 emissions. Though the government of Pakistan is adopting solar PV technology due to its environmental friendliness nature, studies focusing on consumer’s acceptance of solar PV are limited in the country. This research aims to close this knowledge gap by looking into the various considerations that may influence consumers’ willingness to adopt (WTA) solar PV for household purposes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 127 publications
(120 reference statements)
2
55
0
Order By: Relevance
“…We employed the structural equation modeling (SEM) approach for data analysis purposes [57][58][59]. It is a component-focused method adopted to analyze the relational dimensions in the study [60][61][62][63]. PLS-SEM was chosen over all other covariance-based approaches because it enables researchers to analyze both calculations and factor structures.…”
Section: Discussionmentioning
confidence: 99%
“…We employed the structural equation modeling (SEM) approach for data analysis purposes [57][58][59]. It is a component-focused method adopted to analyze the relational dimensions in the study [60][61][62][63]. PLS-SEM was chosen over all other covariance-based approaches because it enables researchers to analyze both calculations and factor structures.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Tanveer et al [46] and Javaid et al [47] explored the role of renewable energy consumption in the climate change risk of countries with high climate vulnerability. The results showed that an increase in the proportion of renewable energy leads to a decrease in risk from climate change.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the 14 th Five-Year Plan and Vision 2035 outline the need to accelerate digital economy development, which provides programmatic guidance for the development of the digital economy (Li Y. et al, 2021;Li Z. et al, 2021). With the development of digital economy, the production and consumption of traditional energy systems under the constraints of supply and demand balance will be changed (Yan et al, 2021), and energy can be controlled, managed, and traded across time and space (Akram et al, 2020;Elavarasan et al, 2021a;Chandio et al, 2021;Tanveer et al, 2021). Therefore, digital economy as a major driver of economic growth is likely to cause disruptions to exist economic processes, systems, and sectors, reshaping the current energy sector under the background of the post-COVID-19 era (Litvinenko, 2020).…”
Section: Introductionmentioning
confidence: 99%